Analisis Kualitas Pelayanan Dengan Metode Importance Performance Analysis (IPA) Dan Costumer Satisfaction Index (CSI) Terhadap Kepuasan Konsumen : Studi Kasus Something Barbershop Sragen - Rahmatul Ahya; Suprapto Suprapto; Jhodi Pratama (Universitas Veteran Bangun Nusantara, 2023)
Small and medium enterprises (UMKM) Are one of the most important parts of the Indonesian economy. Barbershop or barbershop business is one of the UMKM that is growing quite rapidly. Service quality is an important factor in determining whether or not consumers are satisfied. There are several factors that affect customer satisfaction at the barbershop. Namely service quality using the Importance Performance Analysis (IPA) method and service quality using the Customer Satisfaction Index (CSI) method. This study aims to determine whether there is an influence of service quality using Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods on consumer satisfaction in barbershop SMEs in Sragen. The variables used in research II are Quality of Service using the Importance Performance Analysis method (X1), Quality of service using the Customer Satisfaction Index (CSI) method (X2) and Consumer Satisfaction (Y). This study used a purposive sampling technique used to collect quantitative data. The data used in this study are primary data using questionnaire data on MSME actors which are then analyzed using the SPSS software application version 26.0. Based on the analysis that has been carried out, the results show that the average conformity level is 104% with a range of values that are in the range of 92% to 123%. The attribute that has a value of 92% is the addition of lighting in the barbershop area and the attribute that has a value of 123% is a chair for a comfortable haircut. That the result of calculating the Customer Satisfaction Index (CSI) for the quality of service and services of Something Barbershop Sragen is 77.36%. The satisfaction index is in the range of 66-80% which means that overall consumers are satisfied with the quality of service at Something Barbershop Sragen.